Oblique propagation of high-frequency electron-acoustic periodic waves in a nonthermal plasma - Haifa A. Alyousef; Daud Khan; Wilayat Khan; Muhammad Khalid; C. G. L. Tiofack; Samir A. El-Tantawy (AIP Advances)
This study examines the propagation of nonlinear structures in a magnetized, homogeneous plasma model with cold electrons, stationary ions, and nonthermal electrons characterized by a Cairns distribution. The electron-acoustic cnoidal waves (EACWs) in this plasma model are investigated. The reductive perturbation method (RPM) is used to derive the Korteweg–de Vries (KdV) equation. In the form of a cnoidal wave (CW), the solution to the KdV equation is derived. Various plasma parameters, including the concentration of hot electrons, the nonthermal parameter, obliqueness, and the magnetic field, determine the key features of EACWs. In the limiting case, the CW structure can be reduced to a solitary wave (SW) structure. The dispersion and nonlinear coefficients require consideration. We also seek to uncover the connection between the coefficients and these plasma properties, as well as the Sagdeev potential. High-energy electrons are essential for the formation of negative polarity structures. The current plasma model supports rarefactive types of SW and CW.